Transcriptomics supports local sensory regulation in the antenna of the kissing-bug Rhodnius prolixus - Latorre-Estivalis, Jose Manuel (2020)
Background: Rhodnius prolixus has become a model for revealing the molecular bases of insect sensory biology due to the publication of its genome and its well-characterized behavioural repertoire. Gene expression modulation underlies behaviour-triggering processes at peripheral and central levels. Still, the regulation of sensory-related gene transcription in sensory organs is poorly understood. Here we study the genetic bases of plasticity in antennal sensory function, using R. prolixus as an insect model. Results: Antennal expression of neuromodulatory genes such as those coding for neuropeptides, neurohormones and their receptors was characterized in fifth instar larvae and female and male adults by means of RNA-Sequencing (RNASeq). New nuclear receptor and takeout gene sequences were identified for this species, as well as those of enzymes involved in the biosynthesis and processing of neuropeptides and biogenic amines. Conclusions: We report a broad repertoire of neuromodulatory and neuroendocrine-related genes expressed in the antennae of R. prolixus and suggest that they may serve as the local basis for modulation of sensory neuron physiology. Diverse neuropeptide precursor genes showed consistent expression in the antennae of all stages studied. Future studies should characterize the role of these modulatory components acting over antennal sensory processes to assess the relative contribution of peripheral and central regulatory systems on the plastic expression of insect behaviour.